Perencanaan Sistem Plambing Air Bersih dan Air Buangan Gedung SMK Negeri 3 Kota Jambi - Anggrika Riyanti; Marhadi Marhadi; Noviardi Wijaya Saputra (Universitas Batanghari Jambi, 2018)
Plumbing system installation is an important part of building design. To built SMK Negeri 3 Jambi City needs a good plumbing installation design in order to meet the proper resident’s sanitation. The purpose of this study is to design plumbing system for clean water and wastewater at office building SMK Negeri 3 Jambi City. The design of plumbing system based on SNI 03-7065-2005 about Plumbing System Design Standard (Tata Cara Perencanaan Sistem Plambing). The clean water resources is pumped from ground water to the roof tank, then distributed to plumbing units by gravity. The water capacity in office building is calculated at 34,2 m3/day. Roof tank capacity collects clean water in amount of 7600 liter a day, using double roof tank with each capacity is 5000 liter. The roof tank placed on a tower with 1,71 m high. Diameter of clean water pipes are 50-65 mm. The power of water pump is 0,77 kW. The wastewater distribution system uses a separate system, where grey water delivered to Wastewater Treatment Plant and black water delivered to septic tank. Diameter of grey water pipes are 65-75 mm, while diameter of black water pipes are 100 mm. Type of pipe used in this plumbing installation is Polyvinyl Chloride (PVC). Key words : Clean water; Wastewater; Plumbing system.